Rare renal tumor: a case report of juxtaglomerular cell tumor and literature review - Zhu, Cheng; Tian, Zhong; Zhang, Yingfang; Yang, Tingting; He, Zhongcong; Chen, Shicheng; Yu, Bo; Zhang, Neng; Fu, Ni (Frontiers in Oncology, 2025)
Juxtaglomerular Cell Tumor (JGCT) is an extremely rare neoplasm of the kidney that poses a significant clinical challenge in terms of accurate diagnosis. The key to successful treatment lies in the accurate identification of renal lesion. Excessive secretion of renin by JGCT causes activation of renin-angiotensin-aldosterone system (RAAS) secondary to uncontrollable hypertension, hypokalemia and consequently a range of clinical manifestations. While most JGCTs are benign, there have been reports of malignant cases, thus requiring close follow-up. In this case report, the subject is a middle-aged female patient who has suffered from recurrent poorly controlled blood pressure for a number of years. Following a medical examination, the patient was found to have the right renal mass, which was pathologically confirmed to be JGCT after laparoscopic partial right nephrectomy. Thereafter, the patient’s blood pressure recovered steadily during the subsequent follow-up period. Furthermore, a comprehensive summary of the diagnosis, differential diagnosis, treatment and review of case reports of JGCT from the last decade is provided, encompassing malignant biological behaviors.